Situasi Vektor Malaria di Desa Buayan dan Ayah Kabupaten Kebumen Jawa Tengah - Hasan Boesri; Tri Suwaryono (ASPIRATOR - Journal of Vector-borne Disease Studies, 2011)
Abstracts. Some Anopheles species were found in Buayan village. There were An. aconitus,An. annularis, An. barbirostris, An. kochi, An. sundaicus, An. subpictus, An. tesselatus andAn. vagus. The result of ovaries surgery in Buayan village showed that An. aconitus, andAn. vagus were suspiciously to be malaria vector. Furthermore, An. aconitus, An. barbirostris,An. kochi, An. sundaicus, An. subpictus, An. tesselatus, and An. vagus were also foundin Ayah village. As a result of ovaries surgery An. sundaicus and An. vagus were suspiciouslyto be malaria vector in this area. An. vagus habitats were found on the rice field and somegutters, whether An. sundaicus were found on the lagoon and surrounding gutters near thebeach.